2014
DOI: 10.1021/cs5015749
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Early Stages of the Methanol-to-Olefin Conversion on H-SAPO-34

Abstract: Little is known on the early stages of the methanol-to-olefin (MTO) conversion over H-SAPO-34, before the steady-state with highly active polymethylbenzenium cations as most important intermediates is reached. In this work, the formation and evolution of carbenium ions during the early stages of the MTO conversion on a H-SAPO-34 model catalyst were clarified via 1 H MAS NMR and 13 C MAS NMR. Several initial species (i.e., three-ring compounds, dienes, polymethylcyclopentenyl, and polymethylcyclohexenyl cations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
216
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(228 citation statements)
references
References 51 publications
12
216
0
Order By: Relevance
“…These are predominant species during the induction time (see Scheme 1) and can further act as methylating agents during the MTO reaction. 19,26,27,29,90 In this view the work of Hunger et al is worth mentioning, as they pretreated zeolite catalysts to cover the acid sites with methoxides to demonstrate the role and high reactivity of surface methoxides during the induction period and product formation of the MTO process. 19,91,92 From the thermodynamic point of view, water can impact the formation of methoxide species by shifting the equilibrium towards the formation of methanol.…”
Section: Methanol Reactivity During the Early Stages Of The Mto Convementioning
confidence: 99%
See 2 more Smart Citations
“…These are predominant species during the induction time (see Scheme 1) and can further act as methylating agents during the MTO reaction. 19,26,27,29,90 In this view the work of Hunger et al is worth mentioning, as they pretreated zeolite catalysts to cover the acid sites with methoxides to demonstrate the role and high reactivity of surface methoxides during the induction period and product formation of the MTO process. 19,91,92 From the thermodynamic point of view, water can impact the formation of methoxide species by shifting the equilibrium towards the formation of methanol.…”
Section: Methanol Reactivity During the Early Stages Of The Mto Convementioning
confidence: 99%
“…6,[20][21][22][23][24] So far there is no full consensus concerning the mechanism governing the formation of such HP species. [25][26][27] One possibility concerns condensation reactions between initially formed ethene and/or propene, which might undergo oligomerization and cyclization reactions. 25,27 Previous experimental studies on the effect of feed composition on the MTO process suggested that water might alter the adsorption/desorption behavior of these primary products and as such impact their reactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Interestingly,Hunger and co-workers showed already in 2006 that traces of organic impurities neither have any significant influence on product distribution, nor do they govern the formation of HCP species. [10] Since then, the research groups of Hunger, [10][11][12][13][14][15] Kondo, [16] Fan, [17,18] CopØret and Sautet, [19] and Lercher [20] have provided both experimental and theoretical evidences in support of the direct mechanism during the initial stages of the MTO process. Thee arlier proposed direct MTO routes include the a) oxonium ylide,b )carbene,a nd c) methane-formaldehyde mechanisms.…”
mentioning
confidence: 99%
“…Theo bserved bands at 297, 350, 479, and 640 nm are attributed to neutral methylated benzenes,dienylic carbocationic/methylbenzenium (up to three methyl groups) ions, trienylic and methylated poly-arenium ions,r espectively. [10][11][12][28][29][30] Similarly,t he 387 nm band is characteristic for ah examethylbenzenium ion (HMB + )a nd its bathochromic shift to 414 nm with increasing time-on-stream can be explained by the further methylation of HMB + to,f or example,h epta-methylbenzenium ions. [31] We propose that the cracking of polyaromatics into trienylic carbenium species and olefins are responsible for the concomitant increase and decrease of the 479 and 640 nm bands,r espectively,a fter 10 minutes of reaction (Figures S3b).…”
mentioning
confidence: 99%